“I just want to graduate!”: Proposal of Cultural Digital Activities as a Tool to Increase Motivation in the Spanish Language Lab - Company Almagro, Rebeca (BELT - Brazilian English Language Teaching Journal, 2021)
Motivating L2 students is challenging. Most learners are not interested in the language and must be reassured that learning a new language is beneficial and worth the effort (Krashen, 2015). L2 students are more likely to be successful when highly motivated (Schütz, 1998), which can be achieved with fun and engaging material. Games are one of the most motivating techniques when introduced properly (McCallum, 1980). They create a relaxed challenging atmosphere of healthy competition that increases students’ desire of self improvement and makes them forget the anxiety that is usually associated with language lessons (Schumann 1994; Constantinescu, 2012; Gozcu & Caganaga, 2016). The link between motivation and acquisition is positive especially when motivation is intrinsic (Tremblay & Gardner, 1995). However, getting students’ interest is more difficult when their motivation is instrumental. This is the case of Gardner-Webb University students, who are required to take a language course in order to graduate. Motivating these students is harder when the target is culture. Culture has been traditionally taught with old-fashioned teacher-centered activities, but new technologies enable the development of effective and stimulating material (Dema & Moeller, 2012). The present paper focuses on a series of technology-based games addressing culture. The activities were used to increase the motivation of American university students learning Spanish as a L2 at Gardner-Webb University (North Carolina). The experience was designed by a team of Fulbright fellows to be implemented in their Spanish labs as part of the celebration of two Cultural Weeks during the first semester.